2009
DOI: 10.1016/j.crte.2008.11.004
|View full text |Cite
|
Sign up to set email alerts
|

A rootless suture and the loss of the roots of a mountain chain: The Variscan belt of NW Iberia

Abstract: Ophiolites of different Paleozoic ages occur in North-West (NW) Iberia in a rootless suture representing the remnants of the Rheic Ocean, Associated allochthonous terranes in the hanging-and foot-walls of the suture derive from the former margins.whereas the relative autochthon corresponds to the Paleozoic passive margin of northern Gondwana, The Paleozoic tectonic evolution of this part of the circum-Atlantic region is deduced from the stratigraphical. petrological. structural and metamorphic evolution of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
107
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 228 publications
(111 citation statements)
references
References 58 publications
1
107
0
3
Order By: Relevance
“…The supercontinent Pangaea assembled from the collision between Gondwana and Laurussia, following the closure of the Rheic Ocean dur ing the Upper Paleozoic (Matte, 1986;Scotese, 1997;Stampfli and Borer, 2002;Martinez Catalan et al, 2009 (Martinez Catalan et al, 1996). There is a lack of consistent indicators of along-strike components during the subduction, so ideas about the early relative plate movement between the two main land masses involved in the assembly of Pangaea are highly speculative (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The supercontinent Pangaea assembled from the collision between Gondwana and Laurussia, following the closure of the Rheic Ocean dur ing the Upper Paleozoic (Matte, 1986;Scotese, 1997;Stampfli and Borer, 2002;Martinez Catalan et al, 2009 (Martinez Catalan et al, 1996). There is a lack of consistent indicators of along-strike components during the subduction, so ideas about the early relative plate movement between the two main land masses involved in the assembly of Pangaea are highly speculative (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Distribution of continental blocks based on Stampfli and Kozur (2006), Golonka (2007) and Sibuet et al (2012). within the Variscan Belt (e.g., Arenas and Martínez Catalán, 2003;García-Navarro and Fernández, 2004;Martínez Catalán et al, 2009). Several authors have suggested that after the main phase of Variscan deformation, there was a period of delamination and crustal collapse with an associated increased heat flow responsible for renewed igneous activity in central and NW , which was probably promoted by orocline bending (Gutiérrez-Alonso et al, 2008, 2011, 2012Weil et al, 2010Weil et al, , 2013Pastor-Galán et al, 2013).…”
Section: Tectonic Frameworkmentioning
confidence: 99%
“…1 and 2). This suture is rootless and problems exist for a clear correlation with the other suture zones described in the belt, although it is generally accepted that all of them correspond to a unique, more or less complex, oceanic domain, the Rheic Ocean (Simancas et al, 2005;Martínez Catalán et al, 2009). The allochthonous complexes show a late Variscan synformal structure and they are considered to be large klippens composed of several terranes, stacked in a huge and structurally intricated nappe pile (Fig.…”
Section: Geological Contextmentioning
confidence: 99%